2018
DOI: 10.1007/s12028-018-0597-6
|View full text |Cite
|
Sign up to set email alerts
|

Enteral Nutrition Initiation in Children Admitted to Pediatric Intensive Care Units After Traumatic Brain Injury

Abstract: Children with severe TBI and higher ISS were more likely to have delayed initiation of enteral nutrition. Delayed enteral nutrition was an independent risk factor for worse functional status at ICU discharge for the entire cohort, but not for the severe TBI group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
19
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 24 publications
1
19
0
3
Order By: Relevance
“…In our study the difference was 7.1 days, Haney et al 4 the difference between early and late EN was 10.7 days versus 12.9 days, and Mehta et al 11 the difference was 8.7 days versus 10.7 days. The benefits of early EN were also identified in children with cranial trauma through a multicenter study conducted by Balakrishnan et al 12 in which patients who received early nutrition (within 48 hours of admission) had lower disability at discharge and a shorter PICU-LOS of 16 days versus 20 days for those who received late EN. 14 Again, the finding of a shorter PICU-LOS is applicable to multiple geographic settings and pediatric patients with critical illness or injury.…”
Section: Discussionmentioning
confidence: 99%
“…In our study the difference was 7.1 days, Haney et al 4 the difference between early and late EN was 10.7 days versus 12.9 days, and Mehta et al 11 the difference was 8.7 days versus 10.7 days. The benefits of early EN were also identified in children with cranial trauma through a multicenter study conducted by Balakrishnan et al 12 in which patients who received early nutrition (within 48 hours of admission) had lower disability at discharge and a shorter PICU-LOS of 16 days versus 20 days for those who received late EN. 14 Again, the finding of a shorter PICU-LOS is applicable to multiple geographic settings and pediatric patients with critical illness or injury.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, reasonable nutritional support after injury was of great significance for patients to reduce hypoproteinemia and hypermetabolic state, and to promote recovery. 11 In clinical practices, common nutritional support includes parenteral and enteral nutrition. A meta-analysis suggested that early enteral nutrition support after head injury had obvious advantages in improving the prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, reasonable nutritional support after injury was of great significance for patients to reduce hypoproteinemia and hypermetabolic state, and to promote recovery. 11 …”
Section: Discussionmentioning
confidence: 99%
“…По результатам ряда исследований было доказано, что продукция эндогенных цитокинов, ответственных за SIRS, стимулируется бактериальными эндотоксинами, которые абсорбируются кишечником, не участвующим в функции пищеварения [3,4]. Другие исследования показали снижение тяжести и частоты развития септических осложнений, у пациентов на энтеральном питании, после тяжелых механических и термических травм [5][6][7], а также после объёмных оперативных вмешательств [8]. Кроме того, результаты исследований свидетельствуют о том, что энтеральное питание поддерживает нормальную барьерную функцию кишечника, что снижает риски транслокации кишечной флоры и всасывания токсинов в кишечнике [2,7].…”
unclassified
“…Другие исследования показали снижение тяжести и частоты развития септических осложнений, у пациентов на энтеральном питании, после тяжелых механических и термических травм [5][6][7], а также после объёмных оперативных вмешательств [8]. Кроме того, результаты исследований свидетельствуют о том, что энтеральное питание поддерживает нормальную барьерную функцию кишечника, что снижает риски транслокации кишечной флоры и всасывания токсинов в кишечнике [2,7]. Учитывая вышесказанное, можно предположить, что энтеральное питание у пациентов с острым панкреатитом также снизит тяжесть и частоту развития иммунного воспалительного ответа, что в свою очередь улучшит результаты лечения.…”
unclassified